ANTIOXIDANT ACTIVITY OF LEAF EXTRACTS OF HEMIDESMUS INDICUS (L.) R.BR. (ASCLEPIADACEAE). - H, Abdul Kaffoor; K, Muthuraj; K, Arumugasamy (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: A number of Indian medicinal plants have been used for thousands of years in a traditional system of medicine. Hemidesmus indicus is an important member of the Asclepiadaceae family. It is an endemic to the southern Western Ghats, India. The aim of the study was to investigate the free radical scavenging activity of H. indicus. Methods: The aqueous and methanol leaf extracts of H. indicus were assayed for radical scavenging activity, using the stable free radical 2,2-diphenyl- 1-picryl-hydrazyl-hydrate and 2,2'-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid). Results: The results revealed that the IC50 values of aqueous extract of H. indicus were found to be higher than that of the other solvent extracts. The free radical scavenging activity of the plant extracts may be due to the presence of phytoconstituents. Conclusion: In all the methods, the aqueous extract has exhibited the good scavenging activity and this arises that the plant has a potential antioxidant agent.